Factors associated with long-term mechanical ventilation in patients undergoing cardiovascular surgery - Rahimi, Shahram; Abdi, Alireza; Salari, Nader; Shohaimi, Shamarina; Naghibeiranvand, Mehran (BioMed Central, 2023)
One of the main therapy for coronary artery disease is surgery. Prolonged mechanical ventilation in patients with cardiac surgery is associated with high mortality. This study aimed to determine the factors related to long-term mechanical ventilation (LTMV) in patients undergoing cardiovascular surgery.The present study was a descriptive-analytical study in which the records of 1361 patients who underwent cardiovascular surgery and were on a mechanical ventilator during 2019–2020 at the Imam Ali Heart Center in Kermanshah city were examined. The data collection tool was a three-part researcher-made questionnaire including demographic characteristics, health records, and clinical variables. Data analysis was done using descriptive and inferential statistical tests and SPSS Version 25 software.In this study, of the 1361 patients, 953 (70%) were male. The results indicated that 78.6% of patients had short-term mechanical ventilation, and 21.4% had long-term mechanical ventilation. There was a statistically significant relationship between the history of smoking, drug use, and baking bread with the type of mechanical ventilation ( P < 0.05). Also, based on the regression test, some parameters, such as the history of respiratory conditions, could predict the prolongation of mechanical ventilation. Creatinine levels before surgery, chest secretions after surgery, central venous pressure after surgery, and the status of cardiac enzymes before surgery also affect this issue.This study investigated some factors related to prolonged mechanical ventilation in patients undergoing heart surgery. For optimizing the care and therapeutic measures, It is suggested, healthcare workers have a detailed assessment on patients with factors such as the history of baking bread, history of obstructive pulmonary disease, history of kidney disease, use of an intra-aortic pump, number of respirations and systolic blood pressure 24 h after surgery, creatinine level 24 h after surgery, chest secretions after surgery, and the amount of pre-operative ejection fraction and cardiac enzymes (CK-MB).